INTERCULTURAL TRANSLATIONS OF CHRISTIAN CANONICAL SCRIPTURES (Acta Theologica)
Christian canonical Scriptures may include books from Tanakh, Septuagint and New Testament. Several theories have guided the translation of those books into different languages within the canonical boundaries of Catholic, Orthodox or Protestant churches. Those theories have mostly been more recently inspired by Nida’s functional equivalence theory. However, the Skopos or functionalist theory, as championed by Nord, is now emerging as a new approach without necessarily rejecting all the achievements of functional equivalence. This article aims to show how an intercultural approach goes beyond functional and functionalist theories to integrate canonical insights into the production of the Bible translations.